Dose-dependent heart rate reducing effect of nizatidine, a histamine H2-receptor antagonist. - Hinrichsen, H (1993)
1. Twelve healthy subjects were treated in a randomised placebo-controlled crossover study with placebo, 150 mg, 300 mg, and 600 mg nizatidine, 100 mg pirenzepine, and 300 mg nizatidine plus 100 mg pirenzepine for 1 week each. 2. On the seventh treatment day, heart rate, blood pressure, systolic time intervals, impedance cardiographic and Doppler ultrasound variables were measured. 3. Stroke volume and blood pressure were not altered by nizatidine and/or pirenzepine. By contrast, heart rate and cardiac output significantly (P < 0.05) decreased in a dose-dependent manner 1.5 and 3 h after administration of 300 and 600 mg nizatidine. Treatment with 150 mg nizatidine led to similar though non-significant trends. 4. While a slightly insignificant rise in heart rate was detected with pirenzepine alone, heart rate and cardiac output remained unchanged upon combined nizatidine and pirenzepine treatment as compared with placebo and baseline values. 5. In conclusion, nizatidine reduced heart rate and cardiac output in a dose-dependent manner, whereas this negative chronotropic effect was counteracted by concurrent administration of the anti-cholinergic drug pirenzepine.